Linkages between globalisation, carbon dioxide emissions and governance in Sub-Saharan Africa - Simplice Asongu; Rexon T. Nting; Joseph Nnanna (African Governance and Development Institute (AGDI), 2019)
This study investigates linkages between environmental degradation, globalisation and governance in 44 countries in Sub-Saharan Africa using data for the period 2000-2012. The Generalised Method of Moments is employed as empirical strategy. Environmental degradation is proxied by carbon dioxide emissions whereas globalisation is appreciated in terms of trade openness and net foreign direct investment inflows. Bundled and unbundled governance indicators are used, namely: political governance (consisting of political stability/no violence and "voice & accountability"), economic governance (encompassing government effectiveness and regulation quality), institutional governance (entailing corruption-control and the rule of law) and general governance (a composite measurement of political governance, economic governance and institutional governance). The following main finding is established. Trade openness modulates carbon dioxide emissions to have positive net effects on political stability, economic governance, the rule of law and general governance.
Keywords: C52; O38; O40; O55; P37; 330; Carbon dioxide emissions; Economic development; Africa